PERJANJIAN KREDIT KONVENSIONAL DAN AKAD PEMBIAYAAN SYARIAH DALAM SISTEM PERBANKAN - Miftah Idris (Madani Legal Review, 2017)
In distribution of fund, the system adopted by conventional banking and Islamic banking is almost the same in distributing the fund with the provision of credit and of financing by banks to their customers. There is specifically legal basis of contract (aqad) that distinguishes where conventional banking is based on the contract law in Burgerlijk Wetboek and Islamic banking is based on aqad law stipulated in Islamic Sharia (Islamic Law). Problems studied in this research is how the credit contract in the conventional banking and how aqad financing in islamic banking are actually. To know the problem, it will be used descriptive study using secondary data as the data source of this research and then analyzed qualitatively. Thus concluded that the credit contract is a beginning process between the creditor and debtor which are applied in the conventional banking system in its efforts to develop funds collected and also to utilize the funds with the best. But Islamic banking financing adheresses to the profit and loss sharing system that has a unity concept in facing of risk and benefit and also existed justice in bussiness is the basic principle of Islamic banking system.